Strengthening Health Security through Climate-Resilient Environmental Health Systems: A Narrative Review - Muhammad Fadli Ramadhansyah (Jurnal Serambi Engineering, 2026)
Global health security has expanded beyond its traditional focus on infectious disease control to encompass multidimensional threats arising from climate change, environmental degradation, and social vulnerability. The COVID-19 pandemic demonstrated that medical response capacity alone is insufficient to protect populations without strong and resilient environmental health systems. Therefore, strengthening health security in the post-pandemic era requires the integration of climate resilience into environmental health systems. This study aimed to examine the role of climate-resilient environmental health systems in strengthening global health security during the post-pandemic recovery period. A narrative review method was employed through literature searches in Scopus, PubMed, and Web of Science databases, as well as official reports from international organizations including WHO, IPCC, UNICEF, and UNEP published between 2020 and 2026. The findings indicate that climate change increases multiple public health risks through heatwaves, air pollution, floods, droughts, sanitation disruptions, and the rising incidence of climate-sensitive diseases. The COVID-19 pandemic further highlighted the importance of ventilation, water, sanitation, and hygiene (WASH) systems, waste management, environmental surveillance, and multisectoral governance in supporting public health preparedness. Key resilience strategies include the development of climate-resilient WASH infrastructure, early warning systems, environmental quality monitoring, low-carbon healthcare facilities, and community capacity strengthening. In conclusion, environmental health systems represent a strategic component in building adaptive and sustainable health security amid global climate change challenges.